Reading Between The Shadows: Barthes' Semiotic Analysis of 'The Monstrumologist' Cover Design - Hendratno, Hendratno (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2024)
The book cover design plays a crucial role in attracting readers' attention and conveying the essence of the story within. This article analyzes the cover of "The Monstrumologist" by Rick Yancey, designed by Olvyanda Ariesta, using Roland Barthes' semiotic approach. The analysis explores three levels of meaning: denotation, connotation, and myth. At the denotation level, visual elements such as a dark road, large shadow, red blood, and a big clock are identified and described. At the connotation level, these elements reveal deeper meanings related to themes of horror, threat, and the tension of time. At the myth level, the combination of these visual elements reflects profound cultural and social values about the struggle between good and evil, as well as human fear of the unknown. Furthermore, this article discusses the influence and experimentation of the designer in achieving an engaging and meaningful final design. Through a qualitative approach with an emphasis on literature studies, this article presents a comprehensive analysis of how the visual elements on the cover of "The Monstrumologist" not only attract attention but also convey deep themes within the story. The results of the analysis show that this cover design successfully creates a rich visual narrative and enhances readers' experience of this horror novel.